Whose language is it anyway? Students’ sense of belonging and role of English for Higher Education in the multilingual, South African context - Joubert, M.; Sibanda, B. (South African Journal of Higher Education, 2022)
The current decolonial commitments in Higher Education necessitate a need to deepen our understanding of the relationship between English as a Medium of Instruction (EMI) and students’ sense of belonging, their identity, and epistemological access. This article investigates how EMI influences students’ personal and academic identities as well as their sense of belonging to the higher education space. Using student focus groups, this study is exploratory in nature and informed by the voices of undergraduate and postgraduate Humanities students at a South African university in the Free State. The responses were mixed, but there was general consensus that although English does have a place in higher education and can contribute to their sense of belonging, it also has an adverse effect on their identity; the use of indigenous languages provides them with greater epistemological access. A differentiated approach to multilingualism is a possible way forward.